Analysis of environmental awareness, knowledge, and income Minimarket consumers on reducing the use of plastic shopping bags - Achmad Tarmizi; Muhamad Al Faruq Abdullah (Jurnal Scientia, 2024)
This research aims to determine the positive influence of minimarket consumers' environmental awareness, knowledge, and income on reducing the use of plastic shopping bags: A case study of minimarket consumers in the Ciputat area, South Tangerang. Data collection in this research was carried out using a survey method by distributing 100 questionnaires using an accidental sampling technique. Random sampling technique is sampling if the exact population size is not known. This research uses multiple regression analysis with the SPSS version 26 program to process and analyze research results. The research results concluded that the Environmental Awareness variable had a significant effect on reducing the use of plastic shopping bags, the Knowledge variable had a significant impact on reducing the use of plastic shopping bags, and the minimarket consumer income variable had a significant effect on reducing the use of plastic shopping bags. The environmental awareness, knowledge, and income of minimarket consumers substantially impact lessening the use of plastic shopping bags.